Instrumented gait analysis defines the walking signature of CACNA1A disorders - Indelicato, Elisabetta; Raccagni, Cecilia; Runer, Sarah; Hannink, Julius; Nachbauer, Wolfgang; Eigentler, Andreas; Amprosi, Matthias; Wenning, Gregor; Boesch, Sylvia (Journal of neurology, 2022)
Background Gait disturbances are a frequent symptom in CACNA1A disorders. Even though, data about their severity and progression are lacking and no CACNA1A -specific scale or assessment for gait is available. Methods We applied a gait assessment protocol in 20 ambulatory patients with genetically confirmed CACNA1A disorders and 39 matched healthy controls. An instrumented gait analysis (IGA) was performed by means of wearable sensors in basal condition and after a treadmill/cycloergometer challenge in selected cases. Results CACNA1A patients displayed lower gait speed, shorter steps with increased step length variability, a reduced landing acceleration as well as a reduced range of ankle motion compared to controls. Furthermore, gait-width in patients with episodic CACNA1A disorders was narrower as compared to controls. In one patient experiencing mild episodic symptoms after the treadmill challenge, the IGA was able to detect a deterioration over all gait parameters. Conclusions In CACNA1A patients, the IGA with wearable sensors unravels specific gait signatures which are not detectable at naked eye. These features (narrow-based gait, lower landing acceleration) distinguish these patients from other ataxic disorders and may be target of focused rehabilitative interventions. IGA can potentially be applied to monitor the neurological fluctuations associated with CACNA1A disorders.